Expressive Motion in the Early Films of Mary Ellen Bute. (July 2019) - Moen, Kristian
Between 1935 and 1938, Mary Ellen Bute began her career as a filmmaker with a series of mostly animated films, including Rhythm in Light (1935), Synchromy No. 2 (1936), Parabola (1938) and Escape (1938). This article examines how these films offered an innovative, subtle and purposeful investigation of the potentials of animation to create artistic and expressive motion. Paying close attention to Bute's own writing, the article explores how these films related to Bute's expansive vision of cinema as a new form of kinetic art that was both composed and free-flowing. Drawing upon painting, music, sculpture and chronophotography, Bute's work was highly intermedial, investing these arts and media with the dynamic potentials of filmic and animated motion. Tracing how Bute composed motion, displayed motion and used motion expressively, this article aims to develop our understanding of a pivotal 20th-century filmmaker, while at the same time investigating the distinctive ideas of the aesthetics, forms and effects of animated motion that were articulated in her filmmaking practice and theoretical writing.